What is Shadow Banking? - Claessens, Stijn; Ratnovski, Lev. (Washington, D.C. : International Monetary Fund, 2014)
There is much confusion about what shadow banking is. Some equate it with securitization, others with non-traditional bank activities, and yet others with non-bank lending. Regardless, most think of shadow banking as activities that can create systemic risk. This paper proposes to describe shadow banking as 'all financial activities, except traditional banking, which require a private or public backstop to operate'. Backstops can come in the form of franchise value of a bank or insurance company, or in the form of a government guarantee. The need for a backstop is in our view a crucial feature of shadow banking, which distinguishes it from the 'usual' intermediated capital market activities, such as custodians, hedge funds, leasing companies, et cetera.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet